The Effect of Picture Sequences Strategy On Students' Writing Procedure Text Ability (A Study at the Eleventh Grade Students' of MAN Sipagimbar in 2017/2018 Academic Year) - Nuri Yanni Harahap (JURNAL LINER (Language Intelligence and Educational Research), 2018)
THE EFFECT OF PICTURE SEQUENCES STRATEGY ON STUDENTS’ WRITING PROCEDURE TEXT ABILITY (A Study at the Eleventh Grade Students’ of MAN Sipagimbar) By: NURI YANNI HARAHAP NPM.14080077 Program Study: Pendidikan Bahasa Inggris Institut Pendidikan Tapanuli Selatan Nuriyanni.83@gmail.com Abstract The purpose of the research is to know: 1) the application of using picture sequences strategy. 2) the extent of the students’ writing procedure text ability before and after using picture sequences strategy. 3) whether there is a significant effect of picture sequences strategy on students’ writing procedure text ability at the eleventh grade students of MAN Sipagimbar. This research uses experimental method. The population of this research was all of the eleventh grade students of MAN Sipagimbar. It consist 102 students. Cluster sampling technique was uses to get a sample it consist 30 students. The technique for collecting data by observation sheet and giving test (essay test). The result mean score of the application of picture sequences was 3,25 it was “very good”. Value before using picture sequences strategy was 65.5, it was categorized “enough”. While the mean score of the students’ writing procedure text ability after using picture sequences strategy was 77.8, it was categorized “good”. The result of ttest was 9.81 and ttable was 2.04. It means that there is a significant effect of using picture sequences strategy on students’ writing procedure text ability at the eleventh grade students of MAN Sipagimbar. Keyword: Picture Sequences Strategy, Writing Procedure Text Ability